2020
DOI: 10.18388/abp.2020_5380
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF MS – application in food microbiology

Abstract: Microbiological purity control of food products is of great importance in the food industry. Contaminated food is often characterized by a deteriorated taste, smell, and appearance, and when consumed, it can pose a threat to human health and life. Also, contamination incurs huge financial losses to the food industry. Different methods are used for identification of the microorganisms isolated from food, which are based on phenotypic, immunologic, genetic, and spectroscopic techniques. Unfortunately, these meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…In this method, mass of ions is determined by the difference in flight times, where the ions with the same energy levels are directed towards the detector. MALDI-TOF MS provides accurate mass as good as 0.1 [155,164,165].…”
Section: Matrix-assisted Laser Desorption/ionization Time-of-flight Mass Spectrometrymentioning
confidence: 99%
“…In this method, mass of ions is determined by the difference in flight times, where the ions with the same energy levels are directed towards the detector. MALDI-TOF MS provides accurate mass as good as 0.1 [155,164,165].…”
Section: Matrix-assisted Laser Desorption/ionization Time-of-flight Mass Spectrometrymentioning
confidence: 99%
“…3 ). Today, MALDI-TOF MS is used worldwide as the leading diagnostic instrument for species level identification of medical, pharmaceutical and food-related bacteria [ 45, 46 ] and its use for studying environmental ecosystems is increasing rapidly [ 47 ]. The data produced in the present study demonstrated that MALDI-TOF MS reference libraries, supplemented with reference spectra of the Paraburkholderia species studied, will facilitate species level identification.…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
“…It is a very rapid and easy method in comparison with any other phenotype or genotype identification methods. However, it also has some limitations such as the lack of protein profile of some species in the database and the higher cost of MALDI-TOF MS system [ 13 ].…”
Section: Introductionmentioning
confidence: 99%